Arthroscopically Assisted Treatment of Navicular Osteochondral Defect Using Flowable Collagen, Iliac Crest Bone Marrow Aspirate and Fibrin Glue: A Case Report. Issue 5 (October 2015) - Keller, Thomas C.; Dempsey, Ian J.; Park, Joseph S.
A 32-year-old male recreational athlete presented with activity-related chronic dorsal midfoot pain. Conservative treatment, including a prolonged period of immobilization, physical therapy, nonsteroidal anti-inflammatory drugs, and use of a bone stimulator, failed to resolve his symptoms. Computed tomography and magnetic resonance imaging demonstrated a cystic appearing focus within the navicular in conjunction with a osteochondral lesion within the proximal articular surface of the navicular. This case report presents an arthroscopically assisted treatment of a navicular osteochondral lesion using curettage and backfilling with fibrin glue, flowable collagen, and autogenous bone grafting. Levels of Evidence: Therapeutic, Level IV